การศึกษาการใช้ความรู้เวชศาสตร์ฟื้นฟูโดยแพทย์เวชปฏิบัติ ของโรงพยาบาลชุมชนในประเทศไทย - ทองประเสริฐ, สยาม; โฆวินทะ, อภิชนา (ASEAN Journal of Rehabilitation Medicine, 2015)
The Study on Implementation of Rehabilitation Medicine by Primary Care Physicians at District Hospitals in Thailand Tongprasert S, Kovindha A Department of Rehabilitation Medicine, Faculty of Medicine, Chiang Mai University Objective: To study practice of medical rehabilitation by primary care physicians at district hospitals in Thailand; and to provide topics for rehabilitation medicine course in medical curriculum. Study design: Cross sectional study Setting: Department of rehabilitation medicine, Faculty of Medicine, Chiang Mai University Subjects: Primary care physicians at district hospitals in Thailand Methods: A self-administrative mailed questionnaire survey was delivered to primary care physicians in 712 district hospitals (2 mails per hospital). Results: A total of 529 physicians completed the questionnaire (response rate 37%). Common medical rehabilitation knowledge and skills used during medical practice were pressure ulcer prevention and treatment, writing certification for persons with disability, patient education on physical fitness/therapeutic exercise and chest physical therapy. Patients with musculoskeletal pain, geriatric patients and those with respiratory problems were commonly seen in practice. A high percentage of the participants believed that problem based learning should be implemented in undergraduate rehabilitation medicine course. In addition, a 2-day course of practical rehabilitation medicine for primary care physicians is needed. Conclusion: Necessary rehabilitation medicine topics and learning method for medical curriculum are identified. Continuing medical education on practical rehabilitation medicine is also needed. บทคัดย่อ วัตถุประสงค์: เพื่อศึกษาการใช้ความรู้ด้านเวชศาสตร์ฟื้นฟู โดยแพทย์เวชปฏิบัติในโรงพยาบาลชุมชน และนำข้อมูลมาเป็นแนวทางในการปรับปรุงการจัดการเรียนการสอนหลักสูตรแพทยศาสตรบัณฑิต รูปแบบการวิจัย: การศึกษาภาคตัดขวาง สถานที่ทำการวิจัย: ภาควิชาเวชศาสตร์ฟื้นฟู คณะแพทยศาสตร์ มหาวิทยาลัยเชียงใหม่ กลุ่มประชากร: แพทย์เวชปฏิบัติในโรงพยาบาลชุมชนทั่วประเทศ วิธีการศึกษา: ส่งแบบสอบถามทางไปรษณีย์ ให้แพทย์ที่ทำงานอยู่ในโรงพยาบาลชุมชน 712 แห่ง โรงพยาบาลละ 2 ฉบับ ผลการศึกษา: มีแพทย์ตอบแบบสอบถามกลับจำนวน 529 คน (คิดเป็นร้อยละ 37 ของจำนวนแบบสอบถามที่ส่งไปทั้งหมด) ความรู้เวชศาสตร์ฟื้นฟูที่นำไปใช้บ่อยในเวชปฏิบัติได้แก่ การป้องกันและรักษาแผลกดทับ, การออกเอกสารรับรองความพิการ, การออกกำลังกายเพื่อสุขภาพ/เพื่อการรักษา และการฟื้นฟูสมรรถภาพระบบทางเดินหายใจ กลุ่มผู้ป่วยที่พบบ่อย ได้แก่ ผู้ป่วยเจ็บปวดกล้ามเนื้อ กระดูกและข้อ, ผู้ป่วยสูงอายุ และผู้ป่วยโรคระบบทางเดินหายใจ ผู้ตอบแบบสอบถามส่วนใหญ่ (เกือบร้อยละ 90) เห็นด้วยว่าหลักสูตรแพทยศาสตร์บัณฑิตควรจัดการเรียนการสอนแบบใช้ปัญหาเป็นหลัก และแพทย์เวชปฏิบัติมีความเห็นว่าควรมีการฟื้นฟูวิชาการเรื่องเวชศาสตร์ฟื้นฟู ระยะสั้น 2 วัน สรุป: การศึกษานี้ทำให้ได้หัวข้อเนื้อหาในกระบวนวิชาเวชศาสตร์ฟื้นฟูสำหรับหลักสูตรแพทยศาสตรบัณฑิต และวิธีการจัดการเรียนการสอนที่เหมาะสม อีกทั้งแพทย์เวชปฏิบัติมีความต้องการฟื้นฟูวิชาการเรื่องเวชศาสตร์ฟื้นฟูสำหรับเวชปฏิบัติทั่วไป